Is Science for Everyone? Exploring Intersectional Inequalities in Connecting With Science - Seebacher, Lisa M.; Vana, Irina; Voigt, Christian; Tschank, Juliet (Frontiers in Education, 2021)
Several studies have investigated the way learners connect with science, re-emphasising persisting inequalities in science learning. This article combines the concept of intersectionality with the theoretical lens of science learning ecologies to focus on inequalities in connecting with science: Which factors influence the formation of a positive science attitude of young learners and how does the social background of young learners influence their opportunities of connecting with science, focusing on the intersections of class and gender? Based on a quantitative survey among 1,486 visitors of non-formal science education offers aged between 8 and 21, we analyse important factors for the development of a positive science attitude and investigate structural inequalities. The intersectional perspective was implemented in the sampling, survey design as well as its analysis. Using composite indicators of age and gender as well as gender and educational capital, we avoid a homogenisation of broadly defined groups. The results highlight that the development of a highly positive science attitude – as identified in a stepwise logistic regression model – is linked to supportive social environments, intrinsic motivation, science learning in school as well as regular engagement in arts-based learning and self-directed science learning. The learning ecology perspective illustrates the influence of school on science attitudes in general. From an intersectional perspective, however, our findings demonstrate that the persistence of an androcentric and classist concept of science is not compatible with every learning ecology; male learners from educationally affluent backgrounds are most likely to enjoy science learning and see how science relates to their everyday realities. In turn, however, not only female learners with lower educational capital but also male learners with lower educational capital might find it more difficult to connect with science. The intersectional approach unveiled the multiple ways educational capital and gender shape individual learning ecologies. More equitable science learning spaces and offers have to adapt to a diversity of needs and preferences in order to make science activities enjoyable for all.